An update on the cost of decommissioning in the Gulf of Mexico, 2003-2008. (5th May 2009) - Kaiser, Mark J.; Dodson, Richard; Foster, Matthew
Decommissioning represents the end of the production life cycle of offshore structures, when wells are plugged and abandoned, infrastructure is removed and the site is cleared of debris. Decommissioning operations are generally routine, involving standard, low-technology methods, over distinct stages and relatively short time horizons. The removal of the topside facilities, deck, conductors, piles and jacket is the core of all decommissioning projects and typically the most expensive stage. In this paper, we examine the cost of removal operations in the shallow-water Gulf of Mexico for operations performed by Tetra Applied Technologies LLC between 2003-2008. Our data set consists of 120 projects representing 178 million in expenditures and is the largest group of decommissioning operations to be analysed in the Gulf of Mexico. We summarise cost statistics for removal operations and describe the factors that impact cost. We examine preparation, pipeline abandonment, and removal cost across several levels of categorisation and develop first-order regression models for the cost of removal. [Received: January 7, 2009; Accepted: February 17, 2009]